A new neurosurgical adjustable pressure suction apparatus with a mechanically controlled air inlet: the study of precise regulation and atraumatic suction - Nie, Pan; Chen, Mengxi; Zhang, Jibo; Pan, Meicheng; Gu, Xiqian; Xu, Chengshi; Li, Zhengwei; Zhang, Jianjian; Zhao, Wenyuan; Li, Xiang; Zhang, Jie; Chen, Jincao (Frontiers in Neurology, 2022)
Background: The suction tube is an indispensable operative instrument in neurosurgery. Flexible and reasonable application of suction tube facilitate the neurosurgical operation. Objective: This study is to verify the practicality of adjustable pressure suction tube (APS-tube) and explore the appropriate diameter, tip negative pressure of APS-tube for different intracranial structures. Methods: Brain tissue and carotid artery of rats were sucked by APS-tube. Laser speckle contrast imaging (LSCI) was used to record the blood flow velocity (BFV). We measured the tip negative pressure, diameter, air inlet size of APS-tube, and center negative pressure and calculated their correlation. Intraoperative real-time parameters were recorded. Results: When tip negative pressure exceeded 33.4±1.8kpa and 29.2±2.0kpa, it caused severe damage to carotid arteries and brain tissue of rats, respectively. BFV could not return to the preoperative level 3 minutes after the operation (P<0.05), and this decrease was more pronounced when the suction tube diameter was larger (P<0.05). Tip negative pressure was positively correlated with central negative pressure, negatively correlated with air inlet size, and independent of APS-tube diameter. When important structures such as Motor cortex, brainstem were involved, APS-tube with diameter of 1.5 or 2.0mm were mostly used, and the air inlet was opened for about 0.7-2.1mm to maintain a safe tip negative pressure (7.4-27.9kpa). Conclusion: Inappropriate application of suction tube can cause severe intracranial structural damage, even result in an irreversible reduction in BFV. The APS-tube can liberate the way of holding suction tube and be easily adjusted and maintain relatively stable tip negative pressure.